EP846 Parenchymal splenic metastasis from ovarian cancer; a report of two cases and literature review. (1st November 2019) - Zuhdy, M; Gaballa, K; Hamdy, O; Alghandour, R; Elmadawy, MG; Laimon, Y; Saleh, G; Hosam, A; Saleh, M
Abstract : Introduction/Background: Worldwide, ovarian cancer accounts for 3.4% of newly diagnosed cancer cases and 4.4% of cancer related mortality among females.It spreads mainly through peritoneal dissemination, hematogenous or lymphatic routes, and is optimally managed by cytoreductive surgery.Splenic metastasis from malignant tumors are extremely rare ranging from 2.3 to 7.1% in autopsy studies, and a reported incidence of 1.3% in splenectomy studies. To the best of our knowledge, approximately 24 cases of isolated parenchymal splenic metastasis from ovarian cancer were reported in English based literature. Methodology: We here report 2 cases with parenchymal splenic metastasis from ovarian cancer one case was operated in October 2017 and the other was operated October 2018. Results: The 2 cases were managed by doing splenectomy followed by adjuvant chemotherapy and both now are on follow up with no evidence of recurrence or further metastasis. Conclusion: Splenic metastasis from ovarian cancer is relatively rare. Thorough follow up of ovarian cancer cases including careful clinical examination, Computed tomography and tumor markers assessment when clinically indicated can early detect any recurrence events even isolated splenic recurrence. Splenectomy as a secondary cytoreductive surgery is a safe procedure that leads to achieving improved both survival and quality of life. Disclosure: Nothing to disclose.